Modalities of treatment for sleep disordered breathing - Win Tin; Khin, Maung Ohn (2016)
Sleep disordered breathing is a spectrum of diseases that includes snoring,upper airway resistance syndrome and obstructive sleep apnea.It occurs more in obese males, resulting in hypertension and cardiac complications if untreated.There are various treatments,conservatively and surgically,starting from simple tonsillectomy to multilevel surgeries and multi dicipline.Literature review was carried out on the pathophysiology,clinical presentation , complications ,diagnosis and various treatments,using internet Google,search PubMed.Additional information was obtained by cross referencing,using text and journals in the medical libraries.